MODELING OF GEOMETRIC ANISOTROPIC SEMIVARIOGRAM FOR SOIL INVESTIGATION USING CONE PENETRATION TEST (CPT) IN UNIVERSITY OF BANGKA BELITUNG - Amelia, Ririn
Semivariogram is used to measure the dependence between observations based on a certain distance. If the semivariogram is measured based on the distance and direction, we can use anisotropic semivariogram. For establishing the anisotropic semivariogram, we do identification of anisotropic axis, transformation rotation and scaling. Then we have a standard of range for each direction. The standard range is used to obtain geometric anisotropic semivariogram models. In geotechnical, modelling of anisotropic semivariogram is used to measure the dependence between the values of the observation of the results of soil investigation. The data is used the total of frictional resistance from the results of soil investigation using Cone Penetration Test (CPT). In this thesis, we used anisotropic semivariogram models, especially geometric anisotropy to get the model of data. The geometric anisotropic semivariogram models that suitable with the data of the results of soil investigation are exponential, Gaussian, cubic, cardinal sine, prismatto-magnetic, and prismato-gravimetric. The exponential model has the smallest Sum of Squares Error (SSE) value than the other models. So this model is the most suitable model to describe the results of soil investigation using CPT in University of Bangka Belitung.